Ruminations as predictors of negative and positive effects of experienced traumatic events in medical rescue workers - Nina Ogińska-Bulik; Zygfryd Juczyński (Nofer Institute of Occupational Medicine, 2016)
Background: Emergency service workers are exposed to experienced traumatic events related to the nature of their work. The study aimed at identifying the role of cognitive processes, namely different forms of ruminations, as predictors of consequences of experienced trauma. Material and Methods: The data on 120 medical rescuers (80 men, 40 women) who had experienced in their worksite at least 1 traumatic event in the last 5 years, were analyzed. The age of the participants ranged from 25 to 61 years (mean (M) = 38.07; standard deviation (SD) = 8.92). The following Polish versions of standardized tools were used: the Impact of Event Scale - Revised (IES-R), the Posttraumatic Growth Inventory (PTGI) and the Event Related Rumination Inventory (ERRI). Results: The results of regression analyses indicated 2 significant predictors, intrusive rumination for posttraumatic stress disorder (PTSD) and deliberate rumination for posttraumatic growth (PTG). Conclusions: Ruminations play an essential role in the occurrence of negative and positive outcomes of experienced trauma. The associations between PTSD and PTG, with different forms of ruminations, may be used in therapy, treating the appearance of intrusive rumination as an opportunity to turn towards active engagement in deliberate rumination, that facilitates the occurrence of posttraumatic growth. Med Pr 2016;67(2):201-211